FINANCIAL LITERACY CAPABILITIES IN INCREASING FINANCIAL INCLUSION THROUGH SHARIA FINTECH - Koko Bustami; Muhammad Saifrizal (SEAN Institute, 2022)
Studies on financial literacy in increasing financial inclusion and the use of sharia financial technology in banking make it easier for customers to plan financial goals. The purpose of this study is to determine the ability of financial literacy to increase the understanding and use of sharia financial technology and the ability of financial literacy to increase financial inclusion and the ability of sharia financial technology to increase financial inclusion. Using quantitative methods with SEM analysis. The resultit was found that the ability of financial literacy has an effect on sharia financial technology with an estimated value of 1.038 (103.8%), a significant 0.000. The same results were also found in the ability of financial literacy to influence financial inclusion with an estimated value of 0.633 (63%), a significant 0.000. However, the financial capability of Islamic technology has no effect on financial inclusion with an estimated value of 0.055 (5.5%), a significant 0.576.Financial literacy helps economic development in dealing with economic complexity and instability. Financial well-being and financial literacy are two important factors in determining an individual's quality of life